Gender Dimensions of Roma Inclusion : Perspectives from Four Roma Communities in Bulgaria - World Bank (Washington, DC, 2014)
This study employs a qualitative approach to inform the development of effective Roma inclusion policies and programs in Bulgaria. The Roma are currently among the least integrated minority group in Bulgaria. This study investigates the key factors and mechanisms that promote or inhibit social inclusion of the Roma with the wider Bulgarian society by examining their social norms, agency, and strategic life choices from a gender perspective. The study pursues three research questions to deepen the understanding of Roma communities and their inclusion. These are: (i) what are the key gender-related social norms that influence agency in the Roma communities included in the research, and how do they vary across and within these communities?; (ii) what does agency mean in respect to making strategic life choices, and how does if differ in terms of women and men, and across the communities?; and (iii) what can be drawn from understanding of norms, agency, and life choices that can inform stakeholders in developing policies that will support their inclusion, and thereby the implementation of Bulgaria's national strategy for Roma integration? The study uses the European Union's (EU's) working definition of social inclusion as a lens to analyze Roma communities. This study brings to the fore Roma perspectives while focusing on gender roles that are shaped by their social norms. Further, this study looks at how these norms (and roles) are changing as they encounter the values and practices of the modernization of Bulgaria. This study is organized as follows: chapter one gives introduction and background; chapter two depicts the framework of the study and the methodological approach. Chapter three discusses the findings of the study in terms of gender roles and social norms. Chapter four delves into understanding how social norms and agency influence the strategic life choices of Roma men and women, and consequently if these aid in integrating with the broader Bulgarian society. Chapter five concludes the study by pointing to areas that may be explored further for the development of inclusive policies that will benefit the Roma in Bulgaria.